2019
DOI: 10.3390/ijerph16060913
|View full text |Cite
|
Sign up to set email alerts
|

Potential Health Risks of Chemicals in Car Colorant Products

Abstract: Public concern regarding the use of products with chemicals has increased in Korea, following reports indicating that hazardous chemicals in products, such as disinfectants, can cause fatal lung disease. Despite the widespread use of car colorant products, little is known regarding their potential health risks. The purpose of this study was to determine the potential health risks of substances that exist in car colorant products. Thirteen car colorant products were purchased from the Korean market and 15 commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This substance is widely used as a solvent in cleaning and painting [ 33 ]. Lee et al also concluded that four chemicals, including toluene, ethylbenzene, xylene, and 2-butoxy ethanol may pose health risks in workers that use car colorant products [ 34 ]. 2-butoxy ethanol is known as a respiratory irritant and a suspected human carcinogen [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This substance is widely used as a solvent in cleaning and painting [ 33 ]. Lee et al also concluded that four chemicals, including toluene, ethylbenzene, xylene, and 2-butoxy ethanol may pose health risks in workers that use car colorant products [ 34 ]. 2-butoxy ethanol is known as a respiratory irritant and a suspected human carcinogen [ 35 ].…”
Section: Discussionmentioning
confidence: 99%